Clinical evaluation of fitting toric soft contact lenses to current non‐users. (13th February 2013) - Sulley, Anna; Young, Graeme; Lorenz, Kathrine Osborn; Hunt, Chris
Abstract: Purpose: To evaluate the ease with which astigmats from three groups of current non‐wearers of toric contact lenses can be fitted with current toric soft lenses, and to determine toric lens‐wearing success. Methods: This was a 1‐month, randomized, bilateral, open‐label, daily wear study involving 200 subjects and 16 investigational sites in the UK. Three groups of astigmatic subjects aged from 16 to 60 and with a mean age of 36 years (67 spherical soft contact lens users, SW; 72 contact lens drop‐outs, DO; and 61 neophytes, Neo) were fitted with one of two toric soft lens types: a daily disposable toric soft lens (1 Day Acuvue Moist for Astigmatism, Johnson & Johnson Vision Care) or a 2‐weekly replacement, re‐usable toric soft lens (Acuvue Oasys for Astigmatism, Johnson & Johnson Vision Care). Subjects were evaluated after 1 month of wear and success rates calculated according to pre‐set criteria for acceptable fit, orientation stability, visual acuity, quality of vision, and overall comfort. Results: Eighty‐eight percent of lenses were fitted at the first attempt. Of 198 subjects dispensed with lenses, 182 (92%) completed the study. When analysed by subject group, the success rates according to the pre‐set criteria were 80% (53/66), 74% (52/70), and 70% (39/56) for the SW, DO and Neo groups respectively. Comfort was the most common reason for failure with all three groups; however, visual problems were more common in the DO and Neo groups (13% vs 6%). VA with the study lenses was significantly better in the SW group compared to their habitual lenses. For the DO and Neo groups combined (i.e. spectacle wearers), visual acuity was comparable to their habitual spectacles. Conclusions: A high proportion of astigmats who are not using toric soft contact lenses can be fitted with current lenses. Previous contact lens drop‐outs and neophyte wearers achieve visual acuity comparable to spectacles when fitted with toric soft lenses. Spherical contact lens wearing astigmats achieve superior visual acuity when refitted with toric soft lenses. These findings suggest that many astigmats who are not currently using toric soft contact lenses could do so successfully.